PRINCE2 Agile : an implementation pocket guide : step-by-step advice for every project type - Cooke, Jamie Lynn (IT Governance Publishing, 2016)
Explaining how the structured, management-driven PRINCE2 project governance framework is able to work cohesively with team-driven, quality-focused, responsive Agile methods, this guide clearly discusses how these approaches combine to provide the governance, due diligence and accountability that senior management requires, as well as the responsiveness and flexibility that project delivery teams need in order to do their jobs most effectively. --